PREDIKSI KELANJUTAN STUDI SISWA KE PERGURUAN TINGGI DENGAN NAIVE BAYES - Gentur Wahyu Nyipto Wibowo (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The need for an analysis of the predictions of continuation of student studies to college is a strong reason for this research. Because by knowing the number of students at a school who continue or not continue studies to universities become a reference to improve education services at the school concerned. Naive Bayes is an effective and efficient classification algorithm for data mining and machine learning. So in the research proposed Naive Bayes for predictions of continuation of student studies to college with k-fold validation and confusion matrix. And results from the algorithm Naive Bayes is 86.53%.